9. RESULTS OF COVID-19 PREVENTION AND CONTROL AMONG HEALTHCARE PERSONNEL AND RELEVANT FACTORS AT NGUYEN TRI PHUONG HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: A study conducted from May 2022 to December 2022 aimed to describe the management outcomes and analyze factors related to the management of COVID-19 prevention and control for healthcare workers at Nguyen Tri Phuong Hospital, Ho Chi Minh City. Method: A cross-sectional study with a combined analysis of quantitative and qualitative data. Results: The assessment of COVID-19 prevention and control activities at Nguyen Tri Phuong Hospital showed an average score above 80% for all three years. In 2020, the score was 82.7%, in 2021 it was 96.7%, and in 2022 it reached 98.7% according to the COVID-19 Safety Criteria. The COVID-19 infection rate among healthcare workers after receiving three doses of the COVID-19 vaccine was 45.4%. Doctors and nurses had a higher infection rate compared to other staff groups (p=0.019), clinical and paraclinical departments had a higher infection rate compared to functional departments (p=0.035), and frontline workers had a higher infection rate than those working in indirect and support roles (p=0.029). Several factors influencing the management and prevention of COVID-19 were identified through qualitative surveys, including job position, specialization, adherence to disease prevention regulations, complex disease progression, infrastructure, specialized operational guidelines, policies, and human resources. Conclusion: The assessment of COVID-19 prevention and control activities at Nguyen Tri Phuong Hospital consistently showed an average score above 80% for all three years. Several factors influencing the management and prevention of COVID-19 were identified, including job position, specialization, adherence to disease prevention regulations, complex disease progression, infrastructure, specialized operational guidelines, policies, and human resources.
Keywords: Management, COVID-19, healthcare workers.